Provision of antiretroviral therapy for children in Nelson Mandela Bay: Health care professionals' challenges - Margaret Williams; Dalena R.M. Van Rooyen; Esmeralda J. Ricks (AOSIS, 2018)
Background: The human immunodeficiency virus and/or acquired immune deficiency syndrome (HIV/AIDS) pandemic continues to increase in prevalence worldwide, particularly in South Africa, and includes the often overlooked paediatric population. The provision of paediatric antiretroviral treatment (ART) is as essential for children as for adults, and has numerous obstacles, not least of which is lack of decentralisation of facilities to provide essential treatment. Optimising ART, care and support for HIV-positive children, and their caregivers, at public sector primary health care (PHC) clinics is crucial to improve morbidity and mortality rates in children. Aim: To explore the experiences of health care professionals regarding the provision of ART for children at PHC clinics. Setting: The study was conducted in six PHC clinics in Nelson Mandela Bay Health District, Eastern Cape, South Africa. Methodology: The researchers used a qualitative, explorative, descriptive and contextual research design with in-depth interviews. We used non-probability purposive sampling. Data collected were thematically analysed using Creswell's data analysis spiral. We used Lincoln and Guba's model to ensure trustworthiness. Ethical standards were applied. Results: Health care professionals experienced numerous challenges, such as lack of resources, need for training, mentoring and debriefing, all related to providing decentralised ART for HIV-positive children at the PHC level. Conclusion: Capacitation of the health care system, integration of services, competent management and visionary leadership to invoke a collaborative interdisciplinary team approach is required to ensure that HIV is treated as a chronic disease at the PHC clinic level.